St. Joseph's Church and Ashland, Riley County - Rudder, Tyler (Kansas State University, The Chapman Center for Rural Studies, 2012)
The Ashland and Lower McDowell Creek communities were settled towards the end of the 1800s, but contained a variety of cultural and economic differences. St. Joseph’s Catholic Church worked as an agent to resolve these differences. This study, using census data, plat maps, tombstone inscriptions, and yearbook data, brings these differences to light, to show how St. Joseph’s could bring together its congregation, revealing how early rural churches could act as a uniting force.
Tyler Rudder, “St. Joseph's Church and Ashland, Riley County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/87.
Keywords: St. Joseph's Church; Ashland; Riley County; Geary County; McDowell Creek; Konza Prairie